International students’ adaptation process in a Turkish university - Atila Demir, Sevim; Nam, Dilek; Foley, Lara (Journal of International Students, 2025)
International student mobility increases student diversity, fosters different perspectives, and contributes to human capital. Turkey has gradually increased international student numbers, making investigating their challenges and academic success factors essential. This study examines the adaptation processes of 62 language preparatory students at a state university in northwestern Turkey using an exploratory, qualitative approach, focusing on a holistic single case study design. Semi-structured interviews were conducted, and data were analyzed using a common software tool. The article addresses the adaptation process, structures and practices aiding adaptation, and reasons for choosing Turkey as a study destination. Findings show students choose Turkey for "cultural proximity," "social conditions," and "educational conditions." Adaptation factors are categorized into "cultural practices in daily life," "individual factors," and "institutional factors."